Designing of additional professional programs for academic teaching staff of higher education organizations - Olga V. Igumnova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The idea of lifelong education is realized not only in the form of theoretical concepts, but it is put into practice of the personnel’s training as well. The need for constant professional development is fixed at the legislative level and stated in professional standards for all sectors of activity. Under the current legislation the academic teaching staff of any higher education organization must take advanced training courses at least once every 3 years. Thus, the problem of designing additional professional programs - advanced training programs for the academic teaching staff of higher education organization is relevant. Empirical and theoretical research methods, as well as an analysis of our own program development experience, made it possible to make generalizations about the program design stages, which are presented in this article. The design stages contain the baseline comment on the essence of the developer’s actions and a rough result of the design of the program, both at a separate stage and for the program as a whole. Using the ongoing additional professional program as an example, some substantive units that can be considered as the universal ones conforming to professional standards of the academic teaching staff activities are highlighted. The author points out that all program units should have meaningful interdependencies and in this case they can be typified as a kind of educational case, within which both traditional and innovative teaching methods are applied. A non-standard approach to evaluating the students that participate in advanced training courses is the organization of the end-of-course assessment. It represents the project review that helps the student to demonstrate his improved competences. The proposed stages of designing an additional professional program and organizing work with students contribute to the development of the system of postgraduate education and have practical significance for all educational organizations that develop their own advanced training programs for the personnel.